The Dirt: Industrial Disease and Conflict at St. Lawrence, Newfoundland - Rennie, Rick (Fernwood, 2008)
In the cemeteries of St. Lawrence and several neighbouring towns on the south coast of Newfoundland lie the remains of some 200 workers, killed by the dust and radiation that permeated the area’s fluorspar mines. The Dirt chronicles the many forces that created this disaster and shaped the response to it, including the classic ‘jobs or health’ dilemma, the contentious process of determining the nature and extent of industrial disease and the desire of employers to ‘externalize’ the costs of production onto workers and communities. Central to the account is the persistent effort by workers, women in the community and other activists to gain recognition of health hazards in the mines, their effects on workers and to obtain adequate compensation for victims and their families. –Publisher's description. Contents: Origins of a disaster: working conditions and labour relations in the 1930s – Protest and retreat: the war years – Industry revival, increasing hazards and the recognition of sislicosis, 1946-1956 – More deadly perils: radiation and cancer – "The truly ghastly total" and the lack of compensation coverage – Mounting protest, industry closure, and the legacy of the past.
https://fernwoodpublishing.ca/book/the-dirt
Keywords: Aspect sanitaire; Diseases; Employees; Employees Diseases; Employees Health and hygiene; Fluorspar industry; Health and hygiene; Health and hygiene. Mining; Health aspects; Industrie; Maladies; Mineral dusts; Miners; Newfoundland and Labrador; Newfoundland and Labrador St. Lawrence; Newfoundland and Labrador. Calcium Fluoride; Newfoundland and Labrador. Occupational Diseases; Newfoundland and Labrador. Silicosis; Personnel; St. Lawrence. Fluorite; St. Lawrence. Fluorspar industry; St. Lawrence. Mineral dusts; St. Lawrence. Miners; St. Lawrence. Mineurs; Terre-Neuve-et-Labrador; Toxicologie; Toxicology; Toxicology. Miners